Strategi Peningkatan Disiplin Personil Pemadam Kebakaran pada Dinas Pemadam Kebakaran dan Penanggulangan Bencana Kota Palembang - Mohammad Hardiansyah; Sunarto Sunarto; Ignasius Hendrasmo (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Mohammad Hardiansyah. Strategy to Improve The Discipline of FireFighting Personnel to the Palembang Fire and Disaster Management Service. This study aims to Improve the Discipline of Fire Fighting Personnel to the Palembang Fire And Disaster Management Service. The results show that from the results of research that has been carried out it can be said that the Strategy for Increasing Discipline of Personnel Related to Fire Fighting Services to the Community at the Palembang City Fire and Disaster Management Service has not been effective because there are several indicators that have not been met from the side of external training that are not. can be followed by all personnel due to limited funds, as well as the support of facilities and facilities that are still not supported. For training activities carried out by employees, namely internal training for Levels I, II and III, while external training is held at the DKI Jakarta Fire Department in Ciracas, and has now been implemented by the Ministry of Home Affairs. The supporting factor in this research is where the ASN development policy, as well as agency support for internal training and personal motivation are the main and important things, although in the future there will need to be other improvements. In addition, the existence of rewards and punishments is also a motivation to improve work discipline. Improving the quality of work is apart from the quality of personnel, also in terms of improving supporting facilities and infrastructure, currently the facilities owned are still not in accordance with the needs, so this is the inhibiting factor in this research. Then a lot of fire fighting equipment is still lacking, be it hoses, pumps, for reasons of budget constraints, of course this triggers the fire fire operation process